2021
DOI: 10.1016/j.nbd.2021.105529
|View full text |Cite
|
Sign up to set email alerts
|

Altered neocortical oscillations and cellular excitability in an in vitro Wwox knockout mouse model of epileptic encephalopathy

Abstract: Summary Loss of function mutations of the WW domain-containing oxidoreductase ( WWOX ) gene are associated with severe and fatal drug-resistant pediatric epileptic encephalopathy. Epileptic seizures are typically characterized by neuronal hyperexcitability; however, the specific contribution of WWOX to that hyperexcitability has yet to be investigated. Using a mouse model of neuronal Wwox -deletion that exhibit spontaneous seizures, in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…WWOX is a putative tumor suppressor that encodes a member of the short-chain dehydrogenases/reductase (SDR) protein family, which is also related to epileptic encephalopathy ( Johannsen et al, 2018 ; Repudi et al, 2021 ). WWOX plays an essential role in balancing neocortical excitability, and its deletion can lead to spontaneous seizures in mice ( Breton et al, 2021 ). During neurogenesis and early brain development, loss of WWOX can affect different cytoskeletal components and alter prenatal cortical development ( Iacomino et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…WWOX is a putative tumor suppressor that encodes a member of the short-chain dehydrogenases/reductase (SDR) protein family, which is also related to epileptic encephalopathy ( Johannsen et al, 2018 ; Repudi et al, 2021 ). WWOX plays an essential role in balancing neocortical excitability, and its deletion can lead to spontaneous seizures in mice ( Breton et al, 2021 ). During neurogenesis and early brain development, loss of WWOX can affect different cytoskeletal components and alter prenatal cortical development ( Iacomino et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indepth analysis of WWOX function in the brain is ongoing. Studies in the WWOX knockout mouse model have demonstrated spontaneous bursts of activity in the neocortex, suggesting that WWOX plays a fundamental role in balancing neocortical excitability 17 An exon 6 deletion and an intron 5 deletion were both found on a single allele, suggesting that the chromosome underwent two separate breakage and rearrangement events. This also re ects the WWOX gene encompassing FRA16D from introns 5 to 8, indicating that the WWOX gene is prone to breakages and rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth analysis of WWOX function in the brain is ongoing. Studies in the WWOX knockout mouse model have demonstrated spontaneous bursts of activity in the neocortex, suggesting that WWOX plays a fundamental role in balancing neocortical excitability [17]. WWOX is a hot spot for both germline and somatic copy number variants.…”
Section: Discussionmentioning
confidence: 99%